Non-oriented electrical steel sheet
By optimizing the chemical composition and processing technology of the electromagnetic steel plate, the development of {411}<011> orientation is promoted, and the problems of high manufacturing load and deterioration of magnetic properties in the prior art are solved, and a non-oriented electromagnetic steel plate with high strength and high magnetic flux density is achieved.
Patent Information
- Application Number
- CN202380066154.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-22
- Filing Date
- 2023-09-20
- Publication Date
- 2025-04-25
AI Technical Summary
When the prior art improves the magnetic characteristics of electromagnetic steel plates, there are problems of high manufacturing load and deterioration of magnetic characteristics, especially under compression stress, the magnetic characteristics are not stable enough.
By optimizing the chemical components, particle size after hot rolling and rolling rate in cold rolling, combined with the intermediate annealing and final annealing process, the development of {411}<011> orientation is promoted, thereby improving the magnetic characteristics and strength of the steel plate.
It is realized that a non-oriented electromagnetic steel plate with high strength and high magnetic flux density is obtained without increasing the manufacturing load, and the magnetic characteristics are more stable under compression stress.
Smart Images

Figure BDA0005311519980000211 
Figure BDA0005311519980000221
Abstract
Description
Technical Field
[0001] The present invention relates to a non-oriented electrical steel sheet. This application claims priority based on Japanese Patent Application No. 2022-151497 filed in Japan on September 22, 2022, the contents of which are incorporated herein by reference. Background Art
[0002] Electromagnetic steel sheets are used as materials for the cores (iron cores) of motor equipment. Examples of motor equipment include drive motors installed in automobiles, motors for various compressors represented by air conditioners or refrigerators, and generators for household or industrial use. In such motor equipment, high energy efficiency, miniaturization, and high output are required. Therefore, low iron loss and high magnetic flux density are required for electromagnetic steel sheets used as the iron cores of motor equipment. As a solution, there is texture control. Currently, a technology has been proposed that has an easy magnetization axis within the surface of the steel sheet, which is beneficial in improving magnetic properties and can relatively easily improve the development of integrated tissues (α fibers) through rolling processing in hot rolling and cold rolling, which are necessary processes for steel sheet manufacturing. Specifically, a tissue with a <110> orientation roughly parallel to the rolling direction (RD) is formed.
[0003] Patent Documents 1 to 3 all disclose methods for developing the {100}<011> orientation, and describe lowering the phase transformation temperature and rapidly cooling after hot rolling to refine the texture.
[0004] Specifically, Patent Document 1 states that: cooling to 250°C or below at a cooling rate of 200°C / sec or above within 3 seconds after hot rolling; and no annealing between hot rolling and cold rolling, and the cumulative rolling reduction in cold rolling is set to 88% or above. Thus, it is possible to manufacture an electromagnetic steel sheet with {100}<011> orientation integrated in the steel sheet surface.
[0005] In addition, Patent Document 2 discloses a method for manufacturing an electromagnetic steel sheet containing 0.6 mass % to 3.0 mass % of Al, and describes that an electromagnetic steel sheet having a {100}<011> orientation integrated in the steel sheet surface can be manufactured by the same steps as the method described in Patent Document 1.
[0006] On the other hand, Patent Document 3 also states that: the final rolling temperature in hot rolling is set to be above the Ac3 transformation point, and the steel sheet temperature is cooled to 250°C within 3 seconds after hot rolling; or the final rolling temperature is set to be below the Ac3 transformation point -50°C, and the steel sheet is cooled at a cooling rate higher than the standing cooling. In addition, the manufacturing method described in Patent Document 3 is a method of performing two cold rollings with intermediate annealing, and no annealing is performed between the hot rolling and the first cold rolling, and the cumulative rolling ratio is set to 5 to 15% in the second cold rolling. Thus, it is possible to manufacture an electromagnetic steel sheet with {100}<011> orientation integrated in the steel sheet surface.
[0007] In any of the methods described in Patent Documents 1 to 3, when manufacturing an electromagnetic steel sheet with {100}<011> orientation integrated in the steel sheet surface, when the final rolling temperature in hot rolling is set to Ac3 point or above, it is necessary to immediately quench. When quenching is performed, the cooling load after hot rolling increases. When considering the operation stability, it is preferable to suppress the load of the rolling mill performing cold rolling.
[0008] On the other hand, in order to improve magnetic properties, a technology for developing the {411} orientation rotated 20° from the {100} orientation has been proposed. As a method for developing the {411} orientation, Patent Documents 4 to 7 disclose a technology for developing the {411} orientation, which describes optimizing the grain size in the hot-rolled sheet or strengthening the α fibers in the texture of the hot-rolled sheet.
[0009] Specifically, Patent Document 4 describes cold rolling a hot rolled sheet having a higher integration degree of {211} orientation than {411} orientation, with the cumulative rolling reduction during cold rolling being set to 80% or more. This enables the manufacture of an electromagnetic steel sheet having an integration degree of {411} orientation on the steel sheet surface.
[0010] In addition, Patent Documents 5 and 6 describe setting the billet heating temperature to 700°C to 1150°C, the start temperature of the final rolling to 650°C to 850°C, the end temperature of the final rolling to 550°C to 800°C, and setting the cumulative rolling reduction in the cold rolling to 85 to 95%. Thus, it is possible to manufacture an electromagnetic steel sheet having {100} orientation and {411} orientation integrated on the steel sheet surface.
[0011] On the other hand, Patent Document 7 records that when α fibers are developed in a hot-rolled steel coil steel plate near the surface of the steel plate by a thin strip continuous casting method, etc., the {h11}<1 / h12> orientation, especially the {100}<012> to {411}<148> orientation, will be recrystallized by subsequent hot-rolled plate annealing.
[0012] The inventors of the present invention studied the above technology and found that if the {100}<011> orientation is strengthened to improve the magnetic properties according to Patent Documents 1 to 3, rapid cooling after hot rolling is required, which has the problem of high manufacturing load. In addition, it is recognized that when the steel sheet with the strengthened {100}<011> orientation is used as the material of the riveted iron core, the iron core properties expected from the material may not be obtained. The cause of this was studied and it was found that the {100}<011> orientation changes the magnetic properties due to stress, specifically, the deterioration of the magnetic properties (stress sensitivity) when compressive stress acts increases.
[0013] In addition, the technologies of Patent Documents 4 to 7 clearly show that although the {411} orientation is developed, the integration of the <011> orientation as the in-plane orientation is weak, and the magnetic properties in the direction of 45° from the steel plate rolling direction, which is a characteristic of α fibers, do not become sufficiently high. It is also believed that the following possibility is that the in-plane orientation is not aligned with the <011> orientation, that is, the large deviation from the α fibers is a factor that hinders the aggregation to the {411} orientation as the plane orientation, which is the reason why the magnetic properties are not sufficiently improved.
[0014] In addition, when non-oriented electromagnetic steel sheets are used for the rotor of the motor, not only high magnetic flux density is required, but also high strength is required because of high-speed rotation. In order to achieve high magnetic flux density together with high strength, the development of the {100} plane, which is beneficial to the improvement of magnetic properties based on texture control, is studied. In the prior art, it is developed through special processes such as cold rolling at a high rolling rate of more than 95% or vacuum annealing for more than ten hours, and cost reduction is required in industrial production.
[0015] Prior art literature
[0016] Patent Literature
[0017] Patent Document 1: Japanese Patent Application Publication No. 2017-145462
[0018] Patent Document 2: Japanese Patent Application Publication No. 2017-193731
[0019] Patent Document 3: Japanese Patent Application Publication No. 2019-178380
[0020] Patent Document 4: Japanese Patent No. 4218077
[0021] Patent Document 5: Japanese Patent No. 5256916
[0022] Patent Document 6: Japanese Patent Application Publication No. 2011-111658
[0023] Patent Document 7: Japanese Patent Application Publication No. 2019-183185 Summary of the invention
[0024] Technical problem to be solved by the invention
[0025] In view of the above-mentioned problems, an object of the present invention is to provide a non-oriented electrical steel sheet that achieves both high strength and high magnetic flux density without increasing the manufacturing load.
[0026] Technical means for solving technical problems
[0027] The inventors of the present invention have conducted in-depth research to solve the above-mentioned technical problems. As a result, it has been clarified that it is important to optimize the chemical composition, the grain size after hot rolling, and the rolling rate during cold rolling. Specifically, based on the chemical composition of the α-γ phase transformation system, cooling is performed under prescribed conditions after hot rolling to optimize the grain size, and cold rolling is performed at a prescribed rolling rate. The temperature of the intermediate annealing is controlled within a prescribed range, and annealing is performed after the second cold rolling at an appropriate rolling rate, so that the {411}<011> oriented grains that are usually difficult to develop are easily developed. Based on such insights, the inventors of the present invention have further repeatedly conducted in-depth research and thought of the various schemes of the invention shown below.
[0028] (1) A non-oriented electrical steel sheet, characterized in that:
[0029] It has the following chemical composition:
[0030] In terms of mass%, it contains
[0031] C: 0.010% or less,
[0032] Si: 1.50% to 4.00%,
[0033] Sol.Al: 0.0001%~1.0000%,
[0034] S: 0.010% or less,
[0035] N: 0.0005%~0.0100%,
[0036] Ti: 0.0010% to 0.0050%,
[0037] One or more selected from the group consisting of Mn, Ni, and Cu: 2.50% to 5.00% in total, Co: 0.000% to 1.000%,
[0038] Sn: 0.000%~0.400%,
[0039] Sb: 0.000% to 0.400%, and
[0040] P: 0.000%~0.400%,
[0041] When the Mn content (mass %) is [Mn], the Ni content (mass %) is [Ni], the Cu content (mass %) is [Cu], the Si content (mass %) is [Si], the sol.Al content (mass %) is [sol.Al], and the P content (mass %) is [P], the following formula (1) is satisfied:
[0042] The rest is made up of Fe and impurities.
[0043] When the surface of the steel sheet is measured by a scanning electron microscope with electron backscatter diffraction (SEM-EBSD), the area ratio of the grains with {hkl}<uvw> orientation (within a tolerance of 10°) relative to the entire field of view is recorded as Ahkl-uvw. A411-011 is 15% or more.
[0044] The number density of precipitates is 0.5 / μm 2 ~50 / μm 2
[0045] (2×[Mn]+2.5×[Ni]+[Cu])-([Si]+2×[sol.Al]+4×[P])≧1.5%···(1).
[0046] Effects of the Invention
[0047] According to the present invention, it is possible to provide a non-oriented electrical steel sheet that achieves both high strength and high magnetic flux density without increasing the manufacturing load. DETAILED DESCRIPTION
[0048] Hereinafter, embodiments of the present invention will be described in detail.
[0049] First, the chemical composition of the non-oriented electrical steel sheet and the steel material used in the manufacturing method thereof and the cold-rolled steel sheet used in the manufacturing of the non-oriented electrical steel sheet according to the embodiment of the present invention is described. In the following description, the unit of the content of each element contained in the non-oriented electrical steel sheet or the steel material, i.e., "%", means "mass %" unless otherwise specified. In addition, the numerical range represented by "-" means a range including the numerical values recorded before and after "-" as the lower limit and upper limit.
[0050] The non-oriented electromagnetic steel sheet, cold-rolled steel sheet and steel material of the present embodiment are chemical compositions capable of undergoing ferrite-austenite transformation (hereinafter referred to as α-γ transformation), and have the following chemical compositions: C: less than 0.010%, Si: 1.50% to 4.00%, sol.Al: 0.0001% to 1.0000%, S: less than 0.010%, N: 0.0005% to 0.0100%, Ti: 0.0010% to 0.0050%, one or more selected from the group consisting of Mn, Ni and Cu: a total of 2.50% to 5.00%, Co: 0.000% to 1.000%, Sn: 0.000% to 0.400%, Sb: 0.000% to 0.400%, and P: 0.000% to 0.400%, and the remainder is composed of Fe and impurities. Furthermore, the contents of Mn, Ni, Cu, Si, sol.Al, and P satisfy the prescribed conditions described below. Examples of impurities include substances contained in raw materials such as ores and scraps, and substances contained in the manufacturing process.
[0051] (C: 0.010% or less)
[0052] C hinders grain growth by precipitating fine carbides, thereby increasing iron loss and causing magnetic aging. Therefore, the lower the C content, the better. This phenomenon is significant when the C content is higher than 0.010%. Therefore, the C content is set to be less than 0.010%. In addition, the lower limit of the C content is not particularly limited, but it is preferably set to 0.0005% or more based on the cost of decarburization treatment during refining.
[0053] (Si: 1.50% to 4.00%)
[0054] Si increases resistance, reduces eddy current loss, reduces iron loss, increases yield ratio, and improves punching workability of the iron core. When the Si content is less than 1.50%, these effects cannot be fully obtained. Therefore, the Si content is set to be 1.50% or more. On the other hand, when the Si content is higher than 4.00%, the magnetic flux density decreases, and the punching workability decreases due to excessive increase in hardness, making cold rolling difficult. Therefore, the Si content is set to be 4.00% or less.
[0055] (sol.Al: 0.0001%~1.0000%)
[0056] Sol.Al increases resistance, reduces eddy current loss, and reduces iron loss. Sol.Al also helps to increase the relative size of magnetic flux density B50 to saturation magnetic flux density. Here, the so-called magnetic flux density B50 refers to the magnetic flux density in a magnetic field of 5000A / m. When the sol.Al content is less than 0.0001%, these effects cannot be fully obtained. In addition, sol.Al also has the effect of promoting desulfurization in steelmaking. Therefore, the sol.Al content is set to 0.0001% or more. On the other hand, when the sol.Al content is higher than 1.0000%, the magnetic flux density decreases, the yield ratio decreases, and the blanking workability decreases. Therefore, the sol.Al content is set to 1.0000% or less. In addition, in the range of sol.Al content of 0.0100% to 0.1000%, the amount of iron loss degradation caused by AlN precipitation and hindering grain growth increases, so it is preferred to avoid this concentration range.
[0057] (S: 0.010% or less)
[0058] S is not an essential element, for example, it is contained in steel as an impurity. S precipitates through fine MnS, which hinders recrystallization and grain growth during annealing. Therefore, the lower the S content, the better. This increase in iron loss and decrease in magnetic flux density caused by the hindrance of recrystallization and grain growth are significant when the S content is higher than 0.010%. Therefore, the S content is set to less than 0.010%. In addition, the lower limit of the S content is not particularly limited, but it is preferably set to more than 0.0003% based on the cost of desulfurization treatment during refining.
[0059] (N: 0.0005%~0.0100%)
[0060] N forms fine precipitates such as TiN and AlN, which deteriorates magnetic properties, so the N content is 0.0100% or less. In addition, when TiN as a precipitate is insufficient, the strength is insufficient, so the N content is set to 0.0005% or more. Preferably, the N content is set to 0.0010% or more.
[0061] (Ti: 0.0010% to 0.0050%)
[0062] Ti is an element necessary for solid solution strengthening and fine grain strengthening. When the Ti content is less than 0.0010%, these effects cannot be fully obtained. In addition, when the Ti content is higher than 0.0050%, more TiN is formed as fine precipitates, and the magnetic properties deteriorate. Therefore, the Ti content is set to 0.0010% to 0.0050%. Preferably, the Ti content is 0.0010% to 0.0030%.
[0063] (One or more selected from the group consisting of Mn, Ni, and Cu: 2.50% to 5.00% in total)
[0064] These elements are necessary for the α-γ phase transformation to occur, and at least one of these elements needs to be contained in a total of 2.50% or more. On the other hand, when the total exceeds 5.00%, the cost increases and the magnetic flux density also decreases. Therefore, at least one of these elements is set to a total of 5.00% or less.
[0065] In addition, as a condition for the occurrence of the α-γ phase transformation, the following condition is further satisfied. That is, when the Mn content (mass %) is [Mn], the Ni content (mass %) is [Ni], the Cu content (mass %) is [Cu], the Si content (mass %) is [Si], the sol.Al content (mass %) is [sol.Al], and the P content (mass %) is [P], the following formula (1) is satisfied in terms of mass %.
[0066] (2×[Mn]+2.5×[Ni]+[Cu])-([Si]+2×[sol.Al]+4×[P])≧1.5%···(1)
[0067] When the above-mentioned formula (1) is not satisfied, the α-γ phase transition does not occur, so the magnetic flux density becomes low.
[0068] (Co: 0.000%~1.000%)
[0069] Co is an element effective in causing the α-γ transformation, and thus can be contained as needed, but if contained excessively, the cost increases and the magnetic flux density may decrease. Therefore, the Co content is set to 1.000% or less.
[0070] (Sn: 0.000% to 0.400%, Sb: 0.000% to 0.400%)
[0071] Sn or Sb improves the texture after cold rolling and recrystallization and increases its magnetic flux density. Therefore, these elements can be contained as needed, but excessive contents will make the steel brittle. Therefore, the Sn content and the Sb content are both set to 0.400% or less. As described above, in the case of imparting further effects such as magnetic properties, it is preferred to contain one or more selected from the group consisting of 0.020% to 0.400% Sn and 0.020% to 0.400% Sb.
[0072] (P: 0.000%~0.400%)
[0073] P may be contained to ensure the hardness of the steel sheet after recrystallization, but excessive content may cause steel embrittlement. Therefore, the P content is set to 0.400% or less. In order to provide further effects such as magnetic properties, it is preferred to contain 0.020% to 0.400% P.
[0074] Next, the method for measuring the area ratio of specific oriented grains in the non-oriented electrical steel sheet of the present embodiment is described. The area ratio of specific oriented grains is determined by extracting the target specific orientation (the tolerance is set to 10°, and the tolerance is recorded as within 10° below) from the measurement area of a scanning electron microscope (SEM: Scanning Electron Microscope) with electron backscatter diffraction (EBSD) observed under the following measurement conditions using OMI Analysis 7.3 (manufactured by TSL). The extracted area is divided by the area of the side area to obtain a percentage. The percentage is set as the area ratio of specific oriented grains. Hereinafter, "the area ratio of grains with a crystal orientation of {hkl}<uvw> orientation (within a tolerance of 10°) relative to the measurement area" and "the area ratio of grains with a crystal orientation of {hkl} orientation (within a tolerance of 10°) relative to the measurement area" are sometimes referred to as "{hkl}<uvw> ratio" and "{hkl} ratio", respectively. In the following description of crystal orientation, a tolerance of within 10° is set.
[0075] In the non-oriented electrical steel sheet of the present embodiment, when the surface of the steel sheet is measured by SEM-EBSD, the {411}<011> ratio is set to 15% or more. If the {411}<011> ratio is less than 15%, excellent magnetic properties cannot be obtained. Therefore, the {411}<011> ratio is set to 15% or more, preferably 25% or more.
[0076] In addition, the details of the measurement conditions for obtaining the area ratio of each oriented grain are as follows.
[0077] · Measurement equipment: SEM model "JSM-6400 (manufactured by JEOL)", EBSD detector model "HIKARI (manufactured by TSL)"
[0078] Step interval: 0.3μm (after intermediate annealing, skin-pass rolling), or 5.0μm (after final annealing)
[0079] · Ratio: 1000 times (after intermediate annealing and skin-pass rolling) or 100 times (after final annealing)
[0080] ·Measurement object: The center layer (1 / 2 of the plate thickness) of the Z plane (a cross section obtained by cutting the steel plate in the plate thickness direction) in the center of the C direction of the steel plate
[0081] ·Measurement area: Area greater than 1000 μm in the L direction and greater than 1000 μm in the C direction
[0082] In addition, it is preferred that the surface of the steel plate be measured by SEM-EBSD. Φ=20° Has maximum strength and The maximum strength is obtained at Φ=5-35° among Φ=0-90°. Φ=20° The maximum intensity is synonymous with the maximum intensity in the vicinity of the {411}<011> orientation among the {411}<uvw> orientations. The {411}<011> orientation is superior to the {411}<148> orientation in terms of magnetic properties in the 45° direction. Φ = 20° is more preferably With maximum strength.
[0083] On the other hand, when SEM-EBSD was used to measure the surface of the steel plate, The maximum strength is found at Φ=5-35° among Φ=0-90°, which is equivalent to the maximum strength being found near the {411}<011> orientation among the {hkl}<011> orientation. The {411}<011> orientation has excellent magnetic properties and is less stress-sensitive than the {100}<011> orientation, so the magnetic degradation in the riveted core is small. The maximum strength is obtained at Φ=20 to 30 degrees among Φ=0 to 90 degrees.
[0084] Here, the method for determining the maximum strength in a specific orientation range of a steel plate is described. In the measurement area based on SEM-EBSD, OMI Analysis 7.3 is used to generate an orientation distribution function (ODF) under the following conditions. Then, the generated ODF data is output and the maximum strength in a specific orientation range (in The point where the ODF value is the largest within the specified angle range of Φ is taken as the maximum intensity.
[0085] In addition, the determination method of the ODF strength of a specific orientation in a steel plate is described. In the measurement area based on SEM-EBSD, OMI Analysis 7.3 is used to generate ODF under the following conditions. Then, the generated ODF data is output and the specific orientation (in The ODF value of the orientation (the angle Φ specifies the orientation) is taken as the ODF intensity.
[0086] In addition, the details of the generation conditions of ODF are as follows.
[0087] Series Rank [L]: 16
[0088] Gaussian Half-Width [degrees]: 5
[0089] Sample Symmetry: Triclinic (None)
[0090] Bunge Euler Angles: Φ=0~90°
[0091] Furthermore, the area ratio of grains having a specific orientation (within a tolerance of 10°) with respect to the entire field of view when measured by SEM-EBSD is recorded as follows: When the area ratio of grains having a crystal orientation of {hkl}<uvw> orientation (within a tolerance of 10°) with respect to the entire field of view is recorded as the area ratio Ahkl of grains having a crystal orientation of Ahkl-uvw, {hkl} orientation (within a tolerance of 10°) with respect to the entire field of view, both the following equations (2) and (3) are satisfied.
[0092] A411-011 / A411-148≧1.1···(2)
[0093] A411-011 / A100-011≧2···(3)
[0094] In addition, the magnetic properties are superior when there are more grains with the {411} orientation, and inferior when there are more grains with the {111} orientation. Therefore, it is preferable that the {411} ratio is higher than the {111} ratio, and it is more preferable that the {411} ratio is set to be at least twice the {111} ratio.
[0095] Next, the number density of precipitates in the non-oriented electrical steel sheet of the present embodiment will be described. Here, the precipitates are mainly fine precipitates such as TiN, and fine precipitates such as AlN and MnS are also included as other precipitates. The number density of the precipitates is less than 0.5 pieces / μm 2 On the other hand, the number of precipitates increases, and the number density of precipitates is greater than 50 / μm 2 When the TiN is excessive as a precipitate, the magnetic properties are deteriorated. Therefore, the number density of precipitates in the non-oriented electrical steel sheet is 0.5 pieces / μm 2 ~50 / μm 2 .
[0096] The determination of the number density of precipitates is exemplified by observing the sample using a transmission microscope (TEM) by the extraction replica method and calculating the number density. Specifically, the surface at a depth of 1 / 2 of the plate thickness t from the surface of the steel plate is observed by the extraction replica method using a transmission microscope, and the number of precipitates in a 5μm×5μm field of view is measured in the same sample. Among them, it is set to not include coarse precipitates (equivalent circle diameter of 1μm or more) in the field of view that are not included in the calculation of the number density during observation. Moreover, the number of precipitates is measured in more than 10 fields of view in the same sample, and the average value is calculated as the number density of the precipitates. In addition, image analysis software can be used when measuring the number of precipitates.
[0097] Next, the thickness of the non-oriented electromagnetic steel sheet of the present embodiment is described. The thickness of the non-oriented electromagnetic steel sheet of the present embodiment is not particularly limited. The preferred thickness of the non-oriented electromagnetic steel sheet of the present embodiment is 0.25 to 0.50 mm. Generally, the thinner the plate thickness, the lower the iron loss, but the magnetic flux density also becomes lower. Based on this point, when the plate thickness is greater than 0.25 mm, the iron loss is lower and the magnetic flux density is higher. In addition, when the plate thickness is less than 0.50 mm, low iron loss can be maintained. The more preferred lower limit of the plate thickness is 0.30 mm.
[0098] In addition, in the non-oriented electrical steel sheet of the present embodiment, as excellent magnetic properties, the magnetic flux density B50 in the direction of 45° relative to the rolling direction is preferably 1.70 T or more, and the iron loss W10 / 400 in the direction of 45° relative to the rolling direction is preferably 14 W / kg or less. In addition, regarding strength, the tensile strength is preferably 600 MPa or more.
[0099] The tensile strength was determined by conducting a tensile test in accordance with JIS Z2241:2011 using a JIS No. 5 test piece with the rolling direction of the non-oriented electrical steel sheet as the longitudinal direction.
[0100] The above-mentioned non-oriented electrical steel sheet is characterized by the non-oriented electrical steel sheet manufactured by final annealing. Next, the characteristics of the non-oriented electrical steel sheet before final annealing (after skin pass rolling) will be described.
[0101] The non-oriented electrical steel sheet after skin-pass rolling (before final annealing) of the present embodiment has the following GOS (Grain Orientation Spread) value (Gs). Here, the GOS value is a value obtained by averaging the orientation differences between all measurement points (pixels) in the same grain, and the GOS value becomes higher in grains with more distortion. After skin-pass rolling, when the GOS value Gs is small, that is, in a low distortion state, grain growth due to expansion is likely to occur in the final annealing of the next step. Therefore, the upper limit of the GOS value Gs after skin-pass rolling is set to 3.0. On the other hand, when the GOS value Gs is less than 0.8, the distortion amount is too small, and the final annealing time required for grain growth based on expansion becomes longer. Therefore, the GOS value Gs after skin-pass rolling is set to be greater than 0.8 and less than 3.0.
[0102] Here, the calculation method of Gs in the steel plate is described. The SEM-EBSD data when the crystal orientation is specified is analyzed by OIM Analysis 7.3 to obtain the number average of the GOS values, which is used as Gs.
[0103] In addition, in the non-oriented electromagnetic steel sheet after skin-pass rolling (before final annealing), the larger the α fiber ratio, the more advantageous the magnetic properties after final annealing. Here, the method for measuring the α fiber ratio is described. In the present embodiment, the α fibers are set to the {hkl}<011> orientation. In the measurement area based on SEM-EBSD, OMI Analysis7.3 is used to extract the {hkl}<011> orientation (within a tolerance of 10°). The extracted area is divided by the area of the measurement area to obtain a percentage. This percentage is set as the α fiber ratio.
[0104] In the non-oriented electrical steel sheet after skin pass rolling (before final annealing), the α fiber ratio is set to be 20% or more, preferably 25% or more.
[0105] In addition, in the non-oriented electrical steel sheet after skin temper rolling (before final annealing), the ODF intensity of the {100}<011> orientation is set to 15 or less. Here, the ODF intensity of the {100}<011> orientation is the ODF intensity generated using the SEM-EBSD data when the above crystal orientation is specified. ODF value at Φ = 0°. The {411}<011> orientation is excellent in magnetic properties and has lower stress sensitivity than the {100}<011> orientation, so there is less magnetic degradation in rivet cores, etc. By setting the ODF strength of the {100}<011> orientation after skin-pass rolling (before final annealing) to 15 or less, the {411}<011> orientation after the subsequent final annealing can be strengthened.
[0106] The non-oriented electromagnetic steel sheet of the present embodiment can be widely used in applications requiring magnetic properties (high magnetic flux density and low iron loss) by forming an iron core, and can also be used in applications requiring particularly high strength such as rotors.
[0107] Next, an example of a method for producing a non-oriented electrical steel sheet according to the present embodiment is described. In the present embodiment, hot rolling, cold rolling, intermediate annealing, second soft reduction cold rolling (hereinafter referred to as skin pass rolling), and final annealing are performed.
[0108] In hot rolling, the steel material satisfying the above chemical composition is hot rolled to produce a hot rolled sheet. The hot rolling process includes a heating process and a rolling process.
[0109] The steel material is, for example, a steel billet manufactured by conventional continuous casting, and the steel material of the above composition is manufactured by a well-known method. For example, molten steel is manufactured by a converter or an electric furnace. The manufactured molten steel is subjected to secondary refining by a degassing device or the like to obtain a molten steel having the above chemical composition. The molten steel is used to cast a steel billet by a continuous casting method or an ingot casting method. The cast steel billet can also be opened and rolled.
[0110] In the heating process, the steel material having the above chemical composition is preferably heated to 1100-1200° C. Specifically, the steel material is placed in a heating furnace or a soaking furnace and heated in the furnace. The holding time at the above heating temperature in the heating furnace or soaking furnace is not particularly limited, but is, for example, 30-200 hours.
[0111] In the rolling process, the steel material heated in the heating process is subjected to multiple rolling passes to produce hot-rolled plates. Here, the so-called "pass" means that the steel plate passes through a rolling mill stand having a pair of working rolls and is pressed down. For example, hot rolling can be carried out by using a tandem rolling mill including a plurality of rolling mill stands arranged in a series (each rolling mill stand having a pair of working rolls) to carry out multiple rolling passes, or by reverse rolling with a pair of working rolls to carry out multiple rolling passes. From the perspective of productivity, it is preferred to use a tandem rolling mill to carry out a plurality of rolling passes.
[0112] The rolling process consists of rough rolling in the front stage and final rolling in the rear stage. In the present embodiment, the rolling rate in the final pass of the final rolling is set to be 20% or more. By setting the rolling rate in the final pass of the final rolling to be 20% or more, the dislocation density can be sufficiently increased, and the precipitation sites can be increased. As a result, the number density of precipitates in the non-oriented electromagnetic steel sheet can be controlled within the aforementioned range. When the rolling rate in the final pass of the final rolling is less than 20%, the dislocation density becomes insufficient, and therefore the number density of precipitates in the non-oriented electromagnetic steel sheet cannot be controlled within the aforementioned range. Therefore, the rolling rate in the final pass of the final rolling is set to be 20% or more, preferably 30% or more, and further preferably 35% or more. In addition, the larger the rolling rate in the final pass of the final rolling, the more the number density of precipitates tends to increase, but when the rolling rate in the final pass of the final rolling is too large, the productivity will decrease, so the number density of precipitates is made to exceed 50 pieces / μm only by the rolling rate in the final pass of the final rolling. 2 Here, the rolling reduction rate in the final pass of the final rolling is defined as follows.
[0113] Rolling reduction (%) = (1 - plate thickness after final rolling in final rolling / plate thickness before final rolling in final rolling) × 100
[0114] The rolling in the rolling process (rough rolling and final rolling) is performed at a temperature in the γ domain or the α+γ two-phase domain (above the Ar1 point). That is, hot rolling is performed in such a way that the temperature at the final pass of final rolling (final rolling temperature FT (°C)) becomes above the Ar1 point. In addition, hot rolling is preferably performed in such a way that the final rolling temperature FT becomes below the Ac3 point. By performing hot rolling in such a way that the final rolling temperature FT becomes below the Ac3 point, it is possible to preferably introduce distortion into the grains in combination with the cooling described later, and as a result, A411-011 can be improved. When the final rolling temperature FT exceeds the Ac3 point, distortion cannot be preferably introduced into the grains, and as a result, there is a situation where the desired A411-011 cannot be obtained.
[0115] The Ar1 point can be obtained from the thermal expansion change of the steel plate during cooling at an average cooling rate of 1°C / sec. The Ac3 point and the Ac1 point described below can be obtained from the thermal expansion change of the steel plate during heating at an average heating rate of 1°C / sec.
[0116] Here, the so-called final rolling temperature FT refers to the surface temperature (°C) of the steel plate at the output side of the rolling stand where the final pass of the rolling process is performed in the above-mentioned rolling process in the hot rolling process. The final rolling temperature FT can be measured, for example, by a thermometer provided at the output side of the rolling stand where the final pass of the rolling process is performed. In addition, the final rolling temperature FT, for example, represents the average value of the temperature measurement results of the portion excluding the front end 1 section and the rear end 1 section when the entire length of the steel plate is divided into 10 equal sections in the rolling direction.
[0117] Thereafter, by cooling after the rolling process, austenite is transformed into ferrite, thereby obtaining highly distorted and appropriately fine grains. As cooling conditions, cooling is started after 0.1 seconds through the final pass of final rolling, and immediate quenching is not performed in such a way that the surface temperature of the hot-rolled plate becomes above 300°C and below the Ar1 point after 3 seconds. In this way, by avoiding immediate quenching, no special quenching device is required, which also becomes a manufacturing (cost) advantage. At the preferred crystal grain size without excessive refinement, cold rolling is then carried out, and after intermediate annealing, α fibers are developed, and after the subsequent skin smooth rolling and final annealing, the {411}<011> orientation that is usually difficult to develop can be developed.
[0118] In addition, the texture of the hot rolled sheet is inferred to be a structure in which the unrecrystallized austenite undergoes phase transformation if the immediate quenching is performed, and a structure in which the partially recrystallized austenite undergoes phase transformation if the immediate quenching is omitted. In the case of immediate quenching after the final rolling, the structure after the subsequent final annealing is integrated into the {100}<011> orientation, and in the case of omitting the immediate quenching after the final rolling, the structure after the subsequent final annealing is integrated into the {411}<011> orientation. Therefore, it is believed that in order to strengthen the {411}<011> orientation, it is important to transform the partially recrystallized austenite.
[0119] Here, as cooling conditions, it is preferred to set the conditions such that the average crystal grain size in the hot-rolled sheet before cold rolling becomes 3 to 10 μm. When the grains are excessively coarsened, it is difficult for α fibers to develop after cold rolling and intermediate annealing, and sometimes the desired {411}<011> ratio cannot be obtained. In addition, if it is too fine, the desired {411}<011> ratio cannot be obtained. Therefore, in order to set the average crystal grain size in the hot-rolled sheet before cold rolling to 3 to 10 μm, the temperature is set to be below the Ar1 point within 3 seconds after the final pass of the final rolling. The method for measuring the grain size is, for example, by a cutting method.
[0120] In addition, the surface temperature of the hot-rolled plate 3 seconds after the final pass of the final rolling is measured by the following method. In the hot rolling equipment line of the electromagnetic steel plate, a cooling device and a conveyor line (such as a transfer roller) are arranged downstream of the hot rolling mill. A thermometer for measuring the surface temperature of the hot-rolled plate is arranged on the output side of the rolling stand that implements the final pass of the hot rolling mill. In addition, for the transfer rollers arranged downstream of the rolling stand, a plurality of thermometers are also arranged along the conveyor line. The cooling device is arranged downstream of the rolling stand that implements the final pass. A thermometer is arranged on the input side of the water cooling device. The cooling device may be, for example, a well-known water cooling device or a well-known forced air cooling device. Preferably, the cooling device is a water cooling device. The coolant of the water cooling device may be water or a mixed fluid of water and air.
[0121] The hot-rolled sheet temperature was measured by a thermometer installed in the hot-rolling line, and the temperature was obtained 3 seconds after the final pass of the finish rolling.
[0122] Thereafter, the hot rolled sheet is coiled without annealing, and the hot rolled sheet is cold rolled. Note that the hot rolled sheet annealing referred to herein is, for example, a heat treatment at a temperature of Ac1 point or less and 300° C. or more.
[0123] The hot rolled sheet is not annealed but cold rolled. Cold rolling is performed by, for example, continuous rolling using a tandem mill including a plurality of rolling stands arranged in a row (each of which has a pair of working rolls), and multiple passes of rolling can be performed. In addition, reverse rolling based on a Sendzimir rolling mill having a pair of working rolls or the like can also be performed, and one or more passes of rolling can be performed. From the perspective of productivity, it is preferred to use a tandem mill and perform multiple passes of rolling.
[0124] In cold rolling, cold rolling is performed without annealing during the cold rolling process. For example, when reverse rolling is performed, cold rolling is performed in multiple passes without annealing between the passes. In addition, a reversible rolling mill may be used to perform cold rolling in only one pass. In addition, when cold rolling is performed using a tandem rolling mill, cold rolling is performed continuously in multiple passes (passes in each rolling mill stand).
[0125] In the present embodiment, the rolling reduction ratio RR1 (%) in the cold rolling is preferably set to 75 to 95%. Here, the rolling reduction ratio RR1 is defined as follows.
[0126] Rolling ratio RR1 (%) = (1 - plate thickness after final cold rolling / plate thickness before first cold rolling) × 100
[0127] After the cold rolling is completed, intermediate annealing is then performed. In this embodiment, it is preferred to control the intermediate annealing temperature T1 (°C) below the Ac1 point. When the intermediate annealing temperature exceeds the Ac1 point, part of the microstructure of the steel plate is transformed into austenite, and the distortion in the steel plate is excessively reduced. In addition, when the intermediate annealing temperature is too low, recrystallization will not occur, and during the subsequent skin smooth rolling and final annealing, the {411}<011> oriented grains will not grow sufficiently, and the magnetic flux density will sometimes not increase. Therefore, it is preferred that the intermediate annealing temperature T1 (°C) be set to above 600°C.
[0128] Here, the intermediate annealing temperature T1 (° C.) is the sheet temperature near the extraction port of the annealing furnace (the temperature of the steel sheet surface). The sheet temperature of the annealing furnace can be measured by a thermometer disposed at the extraction port of the annealing furnace.
[0129] In addition, the holding time at the intermediate annealing temperature T1 in the intermediate annealing process can be a time known to those skilled in the art. The holding time at the intermediate annealing temperature T1 is, for example, 5 to 60 seconds, but the holding time at the intermediate annealing temperature T1 is not limited to this. In addition, the speed of heating to the intermediate annealing temperature T1 can also be a known condition. The speed of heating to the intermediate annealing temperature T1 is, for example, 10.0 to 20.0°C / second, but the speed of heating to the intermediate annealing temperature T1 is not limited to this.
[0130] The atmosphere during the intermediate annealing is not particularly limited, but an atmosphere containing 20% H2 and the remainder N2 (dry) is used. The cooling rate of the steel sheet after the intermediate annealing is not particularly limited, and the cooling rate is, for example, 5.0 to 60.0°C / sec.
[0131] When the above conditions are completed to the intermediate annealing, the α fiber ratio (within a tolerance of 10°) of the obtained cold-rolled steel sheet measured by SEM-EBSD is 15% or more. Thus, in order to set the α fiber ratio (within a tolerance of 10°) to 15% or more at the stage before skin pass rolling, it is necessary to set the composition to the α-γ transformation system (the γ constituent elements of Mn, Ni, and Cu are high in concentration, hereinafter referred to as high Mn, etc.), and set the hot rolling to the intermediate annealing to the above conditions, especially the cooling conditions after the final rolling are very important. By transforming from partially recrystallized austenite to ferrite, the hot-rolled sheet with an average crystal grain size of 3 to 10 μm after hot rolling is cold-rolled, and then intermediate annealing is performed, so that α fibers oriented in {411}<011> are easily generated and developed. As mentioned above, if the steel is immediately quenched, the structure in which the unrecrystallized austenite undergoes a phase transformation will be formed, and the structure in which the partially recrystallized austenite undergoes a phase transformation will not be formed. The cold rolled steel sheet manufactured in this manner is subjected to skin pass rolling under the conditions described below and further subjected to final annealing to obtain the non-oriented electrical steel sheet of the present invention.
[0132] After the intermediate annealing, skin pass rolling is performed. Specifically, the cold rolled steel sheet after the intermediate annealing step is rolled (cold rolled) at room temperature in the atmosphere. The skin pass rolling here uses, for example, a reverse rolling mill represented by the Sendzimir rolling mill or a tandem rolling mill.
[0133] In skin pass rolling, rolling is performed without annealing in between. For example, when reverse rolling is performed and skin pass rolling is performed in multiple passes, multiple rolling is performed without annealing between the passes. In addition, skin pass rolling can also be performed in only one pass using a reversible rolling mill. In addition, when skin pass rolling using a tandem rolling mill is performed, rolling is performed continuously in multiple passes (passes of each rolling mill stand).
[0134] As described above, in this embodiment, after introducing distortion into the steel sheet by hot rolling and cold rolling, the distortion introduced into the steel sheet is temporarily reduced by intermediate annealing. Then, skin pass rolling is performed. Thus, the distortion excessively introduced by cold rolling is reduced in the intermediate annealing, and the intermediate annealing is performed, thereby suppressing the {111} grains from preferentially causing recrystallization in the steel sheet surface, and allowing the {411}<011> crystal oriented grains to remain. Then, in the skin pass rolling, an appropriate amount of distortion is introduced into each grain in the steel sheet, and in the final annealing of the next step, it is made to be in a state where grain growth based on expansion is easy to occur.
[0135] In the present embodiment, the reduction ratio RR2 in the skin pass rolling is set to 5 to 20%. Here, the reduction ratio RR2 is defined as follows.
[0136] Rolling ratio RR2 (%) = (1 - plate thickness after final pass in skin-pass rolling / plate thickness before first pass in skin-pass rolling) × 100
[0137] Here, when the rolling rate RR2 is less than 5%, the distortion becomes too small, and the final annealing time required for grain growth based on expansion becomes longer. In addition, when the rolling rate RR2 is higher than 20%, the distortion becomes too large, causing normal grain growth instead of expansion, and {411}<148> or {111}<011> grows in the final annealing. Therefore, the rolling rate RR2 is set to 5 to 20%.
[0138] The number of passes in skin-pass rolling may be only one pass (ie, only one rolling pass) or may be rolling of a plurality of passes.
[0139] As described above, in a steel sheet having an α-γ transformation composition (high Mn etc.), the above-mentioned GOS value and α fiber ratio are obtained by performing recrystallization by intermediate annealing and skin pass rolling under the above-mentioned conditions.
[0140] After skin-pass rolling, final annealing is performed at 750°C to Ac1 point for more than 2 hours. When the final annealing temperature T2 (°C) is set to less than 750°C, grain growth due to expansion will not occur sufficiently. At this time, the integration degree of {411}<011> orientation is reduced. In addition, when the final annealing temperature T2 is higher than Ac1 point, part of the structure of the steel sheet will transform into austenite, and grain growth due to expansion will not occur, and the desired {411}<011> ratio cannot be obtained. In addition, when the annealing time is less than 2 hours, even if the final annealing temperature T2 is 750°C to Ac1 point, grain growth due to expansion will not occur sufficiently, and the integration degree of {411}<011> orientation is reduced. In addition, the upper limit of the annealing time of the final annealing is not particularly limited, but since the effect is saturated even if the annealing time exceeds 10 hours, the preferred upper limit is 10 hours.
[0141] Here, the final annealing temperature T2 is defined as the sheet temperature (the temperature of the steel sheet surface) near the extraction port of the annealing furnace. The temperature of the annealing furnace can be measured by a thermometer disposed at the extraction port of the annealing furnace.
[0142] In addition, the rate TR2 of heating to the final annealing temperature T2 in the final annealing process may be a heating rate known to those skilled in the art, and the holding time Δt2 (seconds) at the final annealing temperature T2 may also be a time known to those skilled in the art. Here, the holding time Δt2 represents the holding time after the surface temperature of the steel plate reaches the final annealing temperature T2.
[0143] The preferred heating rate TR2 to reach the final annealing temperature T2 in the final annealing step is set to 0.1°C / sec or more and less than 10.0°C / sec. If the heating rate TR2 is 0.1°C / sec or more and less than 10.0°C / sec, the grain growth based on expansion occurs sufficiently. At this time, the integration of the {411}<011> crystal orientation is further increased, and the grains in the ND plane at the center of the plate thickness are further less likely to deviate.
[0144] The heating rate TR2 is obtained by the following method. A thermocouple is installed on a steel plate having the above chemical composition and obtained by hot rolling to skin pass rolling to prepare a sample steel plate. The sample steel plate with the thermocouple installed is heated, and the time from the start of heating to reaching the final annealing temperature T2 is measured. The heating rate TR2 is obtained based on the measured time.
[0145] The holding time Δt2 at the final annealing temperature T2 in the final annealing process is more than 2 hours. When the holding time Δt2 is more than 2 hours, the grain growth of the {411}<110> grains is caused by expansion, and the strength is increased by fine grain strengthening. At this time, the integration of the {411}<011> crystal orientation is further increased, and the grains in the ND plane at the center of the plate thickness are also more difficult to deviate. The lower limit of the holding time Δt2 is 2 hours, preferably 3 hours. As mentioned above, the preferred upper limit of the holding time Δt2 is 10 hours, and more preferably 5 hours.
[0146] The atmosphere during the final annealing process is not particularly limited. In the atmosphere during the final annealing process, for example, an atmosphere gas (dry) containing 20% H2 and the remainder N2 is used. The cooling rate of the steel sheet after the final annealing is not particularly limited. The cooling rate is, for example, 5 to 20°C / second.
[0147] In addition, the non-oriented electromagnetic steel sheet may be shipped after skin-pass rolling without final annealing. For example, the process up to skin-pass rolling may be performed in a steel sheet manufacturing company, and the non-oriented electromagnetic steel sheet may be punched or laminated in a core manufacturing company of the shipping target, and then stress relief annealing may be performed as a substitute for final annealing at an annealing temperature of 750°C or more and less than the Ac1 point for an annealing time of 2 hours or more.
[0148] The non-oriented electrical steel sheet of the present embodiment can be manufactured in the above manner.
[0149] The method for producing the non-oriented electrical steel sheet according to the present embodiment is not limited to the above-mentioned production steps.
[0150] For example, in the above-mentioned manufacturing process, shot peening and / or pickling can be performed after hot rolling and before cold rolling. In shot peening, the hot-rolled steel plate is shot peened to destroy and remove the oxide scale formed on the surface of the hot-rolled steel plate. In pickling, the hot-rolled steel plate is pickled. The pickling treatment uses, for example, an aqueous solution of hydrochloric acid as a pickling bath. The oxide scale formed on the surface of the steel plate is removed by pickling. Shot peening can also be performed after hot rolling and before cold rolling, followed by pickling. In addition, pickling can also be performed after hot rolling and before cold rolling without shot peening. Shot peening can also be performed after hot rolling and before cold rolling without pickling. In addition, shot peening and pickling are arbitrary processes. Therefore, both the shot peening process and the pickling process can also be omitted after hot rolling and before cold rolling.
[0151] The method for producing the electromagnetic steel sheet of the present embodiment may further include performing coating after the final annealing. In the coating, an insulating film is formed on the surface of the steel sheet after the final annealing.
[0152] The type of insulating coating is not particularly limited. The insulating coating may be an organic component or an inorganic component, and the insulating coating may contain both organic and inorganic components. Examples of inorganic components include dichromic acid-boric acid, phosphoric acid, and silica. Examples of organic components include conventional acrylic, styrene acrylic, acrylic silicon, silicon, polyester, epoxy, and fluorine resins. Considering the paintability, the preferred resin is an emulsion resin. An insulating coating that exerts adhesive properties by heating and / or pressurizing may also be implemented. Examples of insulating coatings with adhesive properties include acrylic, phenolic, epoxy, and melamine resins.
[0153] In addition, coating is an optional process, and therefore, coating may not be performed after the final annealing.
[0154] In addition, the non-oriented electrical steel sheet of the present embodiment is not limited to the above-mentioned manufacturing method. When the surface of the steel sheet is measured by electron backscatter diffraction (EBSD), the area ratio of grains having a {411}<011> orientation (within a tolerance of 10°) relative to the entire field of view is 15% or more, and the number density of precipitates is 0.5 pieces / μm 2 ~50 / μm 2 , is not limited to the above manufacturing method.
[0155] Example
[0156] Next, the non-oriented electrical steel sheet according to the embodiment of the present invention will be specifically described while showing examples. The examples shown below are only examples of the non-oriented electrical steel sheet according to the embodiment of the present invention, and the non-oriented electrical steel sheet according to the present invention is not limited to the following examples.
[0157] (First embodiment)
[0158] By casting molten steel, an ingot having the composition shown in the following Table 1 is produced. Here, the left side of the formula represents the value of the left side of the above-mentioned formula (1). Thereafter, the produced ingot is heated to the billet heating temperature ST shown in Table 1, hot rolled, and finished rolled at the finishing temperature FT shown in Table 1. Then, after passing the final pass, it is cooled under the cooling conditions shown in Table 1 (the time from the final pass to the start of cooling, and the temperature of the steel plate 3 seconds after the final pass).
[0159] Next, the hot rolled steel sheet was pickled without hot rolled sheet annealing to remove oxide scale, and cold rolled at a rolling ratio RR1 shown in Table 1. Then, intermediate annealing was performed in an atmosphere of 20% hydrogen and 80% nitrogen, and the intermediate annealing temperature T1 was controlled to the temperature shown in Table 1 for 30 seconds.
[0160] Next, No. 11 was removed and skin-pass rolling was performed at the rolling ratio RR2 shown in Table 1. Then, final annealing was performed at the final annealing temperature T2 shown in Table 1 in a 100% hydrogen atmosphere. At this time, the holding time Δt2 at the final annealing temperature T2 was set to 2 hours. In addition, before the final annealing was performed, the GOS value Gs was calculated according to the above-mentioned measurement conditions.
[0161] In addition, in order to investigate the texture after the final annealing, a portion of the steel plate was cut off and the cut test piece was reduced to 1 / 2 thickness. The {411}<011> ratio was obtained by observing the aforementioned measurement conditions in the measurement area based on SEM-EBSD. In addition, regarding the number density of precipitates, the number density was obtained by observing the precipitates under the aforementioned measurement conditions using a transmission microscope with an acceleration voltage set to 200 kV. The results are shown in Table 2.
[0162] In addition, in order to investigate the magnetic properties and tensile strength after final annealing, the magnetic flux density B50 and iron loss W10 / 400 were measured, and the iron loss degradation rate of the iron loss W10 / 50 under compressive stress was obtained as an indicator of stress sensitivity. Regarding the magnetic flux density B50, as a measurement sample, a 55 mm square sample was extracted in two directions of 0° and 45° to the rolling direction. Then, the two samples were measured, and the value in the direction of 45° relative to the rolling direction was taken as the magnetic flux density B50 in the 45° direction, and the average value of 0°, 45°, 90°, and 135° relative to the rolling direction was taken as the full-circle average of the magnetic flux density B50. Regarding the iron loss W10 / 400, among the above-mentioned measurement samples, a sample taken in the direction of 45° to the rolling direction was used to obtain the average value in the 45° direction. In addition, regarding the iron loss degradation rate W10 / 50 under compressive stress, x [%], assuming that the iron loss W10 / 50 under no stress is W10 / 50(0) and the iron loss W10 / 50 under a compressive stress of 10 MPa is W10 / 50(10), the iron loss degradation rate W is calculated by the following formula: x The tensile strength was determined by a tensile test in accordance with JIS Z2241: 2011 using a JIS No. 5 test piece with the rolling direction of the steel plate as the longitudinal direction. Table 2 shows the measurement results.
[0163] W x ={W10 / 50(10)-W10 / 50(0)} / W10 / 50(0)
[0164] [Table 1]
[0165]
[0166] [Table 2]
[0167] Table 2
[0168]
[0169] The underlined conditions in Tables 1 and 2 denote conditions outside the scope of the present invention. Inventive Examples No. 1, No. 4, No. 7, and No. 8 all have good values for magnetic flux density B50, iron loss W10 / 400, iron loss degradation rate, and tensile strength.
[0170] On the other hand, in No. 2 as a comparative example, due to the rapid cooling after the final rolling, the {411}<011> ratio becomes small, and the iron loss degradation rate under the compressive stress is large. In addition, since Ti is not contained, no precipitates mainly composed of TiN are generated, and the precipitates are insufficient as a whole, so the tensile strength is insufficient. In No. 3 as a comparative example, since the sum of one or more selected from the group consisting of Mn, Ni, and Cu is insufficient, and the composition does not undergo α-γ phase transformation, the {411}<011> ratio becomes small, and the magnetic flux density B50 (45° direction), iron loss W10 / 400 and iron loss degradation rate are poor. In No. 5 as a comparative example, since the final rolling temperature FT is lower than the Ar1 point, the {411}<011> ratio is small, and Ti is excessively contained, so the magnetic flux density B50 (45° direction), iron loss W10 / 400 and iron loss degradation rate are poor. In No. 6 as a comparative example, the time from the final pass of finish rolling to the start of cooling was too short, so the {411}<011> ratio was small and the iron loss degradation rate under compressive stress was large.
[0171] In No. 9 as a comparative example, due to insufficient Si, the iron loss W10 / 400 is large. In addition, since it does not contain Ti, no precipitates mainly composed of TiN are generated, and the precipitates are insufficient as a whole, so the tensile strength is insufficient. In No. 10 as a comparative example, since the sum of one or more selected from the group consisting of Mn, Ni, and Cu is excessive, the magnetic flux density B50 is poor in the 45° direction and the average of the entire circumference. In addition, due to segregation, a part of it breaks during cold rolling and becomes two pieces. In No. 11 as a comparative example, since skin smooth rolling is not performed, the {411}<011> rate becomes small, and the magnetic flux density B50 (45° direction), iron loss W10 / 400 and iron loss degradation rate are poor. In No. 12 as a comparative example, since the rolling rate RR2 in the skin-pass rolling was too large, the {411}<011> ratio became small, and the magnetic flux density B50 (45° direction) and iron loss W10 / 400 were poor. In No. 13 as a comparative example, since the billet heating temperature ST was too low, the precipitates mainly including TiN were insufficient as a whole, so the tensile strength was insufficient. In No. 14 as a comparative example, since the rolling rate in the final pass of hot rolling (finish rolling) was less than 20%, the precipitates were insufficient as a whole, and the tensile strength was insufficient.
[0172] Industrial Applicability
[0173] According to the present invention, a non-oriented electrical steel sheet having both high strength and high magnetic flux density can be provided without increasing the manufacturing load, and the industrial value is great.
Claims
1. A non-oriented electromagnetic steel sheet, characterized in that: It has the following chemical composition: In terms of mass%, it contains C: 0.010% or less, Si: 1.50% to 4.00%, Sol.Al: 0.0001%~1.0000%, S: 0.010% or less, N:0.0005%~0.0100%、 Ti: 0.0010% to 0.0050%, One or more selected from the group consisting of Mn, Ni, and Cu: 2.50% to 5.00% in total, Co: 0.000% to 1.000%, Sn: 0.000%~0.400%, Sb: 0.000% to 0.400%, and P:0.000%~0.400%, When the Mn content in mass % is [Mn], the Ni content in mass % is [Ni], the Cu content in mass % is [Cu], the Si content in mass % is [Si], the sol.Al content in mass % is [sol.Al], and the P content in mass % is [P], the following formula (1) is satisfied: (2×[Mn]+2.5×[Ni]+[Cu])-([Si]+2×[sol.Al]+4×[P])≧1.5%···(1) The remainder is composed of Fe and impurities; When the area ratio of {hkl}<uvw> oriented grains within a tolerance of 10° relative to the entire field of view when the steel sheet surface is measured using a scanning electron microscope with electron backscatter diffraction is recorded as Ahkl-uvw, A411-011 is 15% or more, The number density of precipitates is 0.5 / μm 2 ~50 / μm 2 .
Citation Information
Patent Citations
Method for producing non-oriented magnetic steel sheet having high magnetic flux density
JP2011111658A
Electromagnetic steel sheet, and method for producing the same
JP2017145462A
Electromagnetic steel sheet, and method for producing the same
JP2017193731A
Electromagnetic steel sheet, and manufacturing method of electromagnetic steel sheet
JP2019178380A
Nonoriented electromagnetic steel sheet
JP2019183185A